ChemInform Abstract: An Air‐Stable Half‐Sandwich RuII Complex as an Efficient Catalyst for [3 + 2] Annulation of 2‐Arylcyclo‐2‐enones with Alkynes. Issue 30 (July 2016) - Zhao, Yinsong; He, Zhen; Li, Shiqing; Tang, Junbin; Gao, Ge; Lan, Jingbo; You, Jingsong
Abstract: A novel ruthenium complex HSRC is prepared and successfully applied for the synthesis of spiro carbocyclic indenes via a [3 + 2] annulation strategy.